Investigation of the Inter‐ and Intrascanner Reproducibility and Repeatability of Radiomics Features in T1‐Weighted Brain MRI. Issue 5 (9th April 2022) - Mitchell‐Hay, Rosalind Nina; Ahearn, Trevor S.; Murray, Alison D.; Waiter, Gordon D.
Abstract : Background: Radiomics is the high throughput analysis of medical images using computer algorithms, which specifically assess textural features. It has increasingly been proposed as a tool for the development of imaging biomarkers. However, an important acknowledged limitation of radiomics is the lack of reproducibility of features produced. Purpose: To assess reproducibility and repeatability of radiomics variables in brain MRI through a multivisit, multicenter study. Study Type: Retrospective. Population: Fourteen individuals visiting three institutions twice, 10 males with the mean age of 36.3 years and age range 25–51. Field Strength: 3D T1W inversion recovery on three 1.5‐T General Electric scanners. Assessment: Radiomics analysis by a consultant radiologist performed on the T1W images of the whole brain on all visits. All possible radiomics features were generated. Statistical Test: Concordance correlation coefficient (CCC) and dynamic range (DR) for all variables were calculated to assess the test–retest repeatability. Intraclass correlation coefficients (ICCs) were calculated to investigate the reproducibility of features across centers. Results: Of 1596 features generated, 57 from center 1, 15 from center 2, and 22 from center 3 had a CCC > 0.9 and DR > 0.9. Eight variables had CCC > 0.9 and DR > 0.9 in all centers. Forty‐one variables had an ICC of >0.9. No variables had CCC > 0.9, DR > 0.9, and ICC > 0.9. Data Conclusion: Repeatability and reproducibility of variables is a significant limitation of radiomics analysis in 3DT1W brain MRI. Careful selection of radiomic features is required. Level of Evidence: 4 Technical Efficacy Stage: 2